Cellulase production by the Thermophilic Fungus, Thermoascus aurantiacus - Tong, Chow Chin; Cole, Anthony L. J. (1982)
Thermoascus aurantiacus was the most active cellulase producer of several thermphilic fungi tested. The optimum growth temperature for T. aurantiacus in liquid medium was 45° C and maximum cellulase production from filter paper occurred at 40°C. The optimum temperatue for {3-glucosidase and carboxymethylcellulase activity was 70° C; for filter paper degrading activity it was 65°C. Maximum activity was found at pH 5.0 for the filter paper degrading enzyme and glucosidase and pH 4.3 for carboxymethylcellulase activity.